2010
DOI: 10.1177/1090820x10369512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Centrifugation on Cell Composition and Viability of Aspirated Adipose Tissue Processed for Transplantation

Abstract: If centrifuged lipoaspirate is used, the pellet (rich in adipose-derived mesenchymal stem cells) and the middle layer should be employed to increase fat graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 21 publications
3
68
0
5
Order By: Relevance
“…Adipose tissue harvesting and processing techniques employed in the surgery room play an important role on the viability and integrity of adipose tissue, and according our study, also on the percentage of MSC (Condé-Green et al, 2010). A long-term graft is reached mainly by angiogenesis and MSC enhance local angiogenesis by differentiation events, and secretion of angiogenic factors (Hanson et al, 2010).…”
Section: Fat Graft Enriched With Mesenchymal Stem Cellmentioning
confidence: 53%
See 4 more Smart Citations
“…Adipose tissue harvesting and processing techniques employed in the surgery room play an important role on the viability and integrity of adipose tissue, and according our study, also on the percentage of MSC (Condé-Green et al, 2010). A long-term graft is reached mainly by angiogenesis and MSC enhance local angiogenesis by differentiation events, and secretion of angiogenic factors (Hanson et al, 2010).…”
Section: Fat Graft Enriched With Mesenchymal Stem Cellmentioning
confidence: 53%
“…Our study showed similar histological results. We observed that the adipose tissue resulted from centrifuged lipoaspirate samples contained most of adipocytes with disrupted membranes and general extracellular matrix disruption, whereas decantation maintained the adipocytes´ integrity (Figure 2; Condé-Green et al, 2010). We cannot exclude the fact that reducing centrifugation forces will improve MSC recovery on centrifuged lipoaspirates samples, as already described .…”
Section: Adipose Tissue Harvesting and Preparation For Isolating Mesementioning
confidence: 61%
See 3 more Smart Citations